Optimalisasi Desain Frame Sepeda Menggunakan Software Autodesk Inventor 2015 - Sunardi Sunardi (Semesta Teknika, 2017)
Bicycles become one of the environmentally friendly land transportation and are increasingly demanded by wider community. Frame a main component of the bikes that must safely be designed because it is the haviest part compared to the other components. MUSTANG hybrid bikes use steel Hi-Ten (High Tensile Steel) for their frames. The density of such material is relatively high in comparison with other frame materials such as aluminum alloy, carbon fiber, and titanium. Thus, it needs to be redesigned to optimize frames in terms of mass, stress, displacement, and safety factor. This research was first measureing the dimensions of a MUSTANG bike frame. Next, it was drawn, and simulated using Autodesk Inventor Professional 2015 software. Simulation results were then used to optimize the frame design in terms of its mass, stress, strain, displacement and safety factor. The optimized design simulation shows that maximum stress and displacement being 14,75 MPa and 0,01617 mm, respectively. In addition, minimum safety factor and mass being 14,94 and 3,1323 kg, respectively. The optimum bike frame was found at modification frame 5 with maximum stress of 8,40 MPa, maximum displacement of 0,01782 mm, minimum safety factor of 15 and minimum mass of 3,1343 kg.